Le monastère Saint-Pierre d'Osor (Île de Cres) : Sixième campagne d'études archéologiques - Jurković, Miljenko; Čaušecić-Bully, Morana; Marić, Iva; Bully, Sébastien (Hortus Artium Medievalium, 2012)
Abstract In the 2011 campaign the southern and central apses, as well as the southern nave of the abbey church of St Peter, together with its immediate surroundings were excavated. The primary analysis of the eastern part of the Venetian town wall was undertaken as well. The geophysical survey of the western and south-eastern parts of the complex has equally been continued. The initial results allow us to present a phasing of the early Romanesque church, possibly preceded by two earlier churches, as well as to complete the ground plan thanks to the discovery of the former bell-tower, containing a funerary room (maybe a chapel) in its ground level. Furthermore, the monastic topography was clarified by the discovery of a new construction - probably funerary - situated to the south of the church, a structure situated to the south-east easily recognizable as a possible cloister, and finally by the existence of a long monastic building situated in the eastern part of the monastery, and integrated into the Venetian city walls at the end of the Middle Ages.